Building Communities of Practice: Initial Perceptions of an Interdisciplinary Preparation Program for Special Education Teachers and Social Workers - Marsh, Robbie J.; Ness, Heather Baltodano-Van; Brown, Monica (Journal of the American Academy of Special Education Professionals, 2024)
Pedagogical knowledge has been identified as an essential factor for impacting the learning, behavioral, and social emotional outcomes for children with disabilities, particularly students with emotional disturbances (ED). There are many professionals in and out of the school environment who work with children with ED. Oftentimes, these professionals are required to have specialized knowledge and skills. Unfortunately, they acquire these skills and knowledge separate from each other. Therefore, this 5-year interdisciplinary project funded by the U.S. Department of Education, Office of Special Education Programs (USDOE, OSEP) was designed to enhance the skills and knowledge of special education teachers and social workers regarding students with ED. The purpose of this study was to explore participants’ perceptions of interdisciplinary teacher preparation. The study adopted a basic qualitative (i.e., content analysis) design. Each question was analyzed to capture the emerging categories. The results for each question are discussed in detail. Some recommendations for teacher educators and practitioners are provided.